Exosomes derived from induced cardiopulmonary progenitor cells alleviate acute lung injury in mice - Xia Luo-xing; Xiao Ying-ying; Jiang Wen-jing; Yang Xiang-yu; Tao Hua; M Safur Rehman; ukhail; Qin Jian-feng; Pan Qian-rong; Zhu Yu-guang; Zhao Li-xin; Huang Li-juan; et al. (Acta Pharmacologica Sinica; Vol 45, No 8 (August 2024): Acta Pharmacologica Sinica, 2024)
Cardiopulmonary progenitor cells (CPPs) constitute a minor subpopulation of cells that are commonly associated with heart and lung morphogenesis during embryonic development but completely subside after birth. This fact offers the possibility for the treatment of pulmonary heart disease (PHD), in which the lung and heart are both damaged. A reliable source of CPPs is urgently needed. In this study, we reprogrammed human cardiac fibroblasts (HCFs) into CPP-like cells (or induced CPPs, iCPPs) and evaluated the therapeutic potential of iCPP-derived exosomes for acute lung injury (ALI). iCPPs were created in passage 3 primary HCFs by overexpressing GLI1, WNT2, ISL1 and TBX5 (GWIT). Exosomes were isolated from the culture medium of passage 6–8 GWIT-iCPPs. A mouse ALI model was established by intratracheal instillation of LPS. Four hours after LPS instillation, ALI mice were treated with GWIT-iCPP-derived exosomes (5 × 109, 5 × 1010 particles/mL) via intratracheal instillation. We showed that GWIT-iCPPs could differentiate into cell lineages, such as cardiomyocyte-like cells, endothelial cells, smooth muscle cells and alveolar epithelial cells, in vitro. Transcription analysis revealed that GWIT-iCPPs have potential for heart and lung development. Intratracheal instillation of iCPP-derived exosomes dose-dependently alleviated LPS-induced ALI in mice by attenuating lung inflammation, promoting endothelial function and restoring capillary endothelial cells and the epithelial cells barrier. This study provides a potential new method for the prevention and treatment of cardiopulmonary injury, especially lung injury, and provides a new cell model for drug screening.